Impossible subjects. Illegal aliens and the making of modern America - Ngai, Mae M.
In Impossible Subjects, Mae Ngai traces the history of the ?illegal alien? in American law and society. She articulates why and how illegal migration became the central issue in U.S. immigration policy. Ngai revisits inquiries into the fundamental legal status created by the new challenges outlined above vis-à-vis the notion of a liberal democratic society. These challenges, Ngai posits have directly affected the politics of multiculturalism and national belonging up to the present (Ngai, Impossible Subjects 227-264). Ngai argues that the process was very much created by ideas and practices about citizenship, race, and state authority in the 20th century (Ngai, Impossible Subjects 1-14). Ngai moreover does a close reading of the legal framework of restriction that began in the early 20th Century: statutory architecture, judicial genealogies, and administrative enforcement, differential treatment of European and non-European migrants, and long-term effects (Ngai, Impossible Subjects 17-90). In term of method, Ngai?s grounds her extensive analysis on an extensive literature review -- that includes Eric Muller?s Free to Die for Your Country -- as well as wide-ranging archival research that includes unstudied records of the U.S. Border Patrol and the INS. Ngai contribution to American history debates, legal history, and ethnic studies. Impossible Subjects is a sweeping re-examination of U.S. immigration in the 20th century. In historical/cultural analysis, Ngai examines the immigration legacy of Filipinos, Mexicans, Japanese, and Chinese ? a foursome that, in at least one way, encountered aspects of illegal alieness, alien citizenship, colonial subjectivity, and were imported contract workers (Ngai, Impossible Subjects 91-224). Ngai brings to presence how immigration policy, specifically national-origin and numerical quotas, re-shaped the US by creating both new categories of racial difference and by giving emphasis to land borders and their policing (Ngai, Impossible Subjects 22, 25-27, 32-37, and 89, 249-254). The confluence of these phenomena gave rise to the category of illegal alien, a new legal and political Filipino Nationals, Braceros, Nisei Renunciators, and Paper Sons challenged conventional forms of subjectivity whose participation in the nation was a social truism but a legal problem. Individual members of the categories previously outlines became subject devoid of rights and barred from citizenshipáginas: